(untitled) (Biological Sciences - PJSIR, 2022)
Thermal, infrared spectral and chemical analyses have been carried out on fourteen rock phosphate samples from five deposits in Hazara, North West Frontier Province (NWFP), Pakistan. Samples with high phosphate content have shown less than 3% loss in weight on ignition and a set of two characteristic medium intensity absorption bands in the range 1460-1420cm’. On the other hand ores samples with low phosphate content have shown high loss in weight on ignition and only one absorption band around 1460-1420cm’ in their infrared spectra. The analytical data described and discussed in this paper suggests that TGA/DTA and infrared spectral techniques may be used as a rapid means for the preliminary selection of ore-grades, in place of conventional techniques.